A Multimodal Analysis of Tokopedia X BTS Advertisement - Sherania Rahmah Salsabila; Suparto Suparto (ITScience (Information Technology and Science), 2023)
One of the texts with nuanced meanings is an advertisement. When discussing how to effectively convey messages in advertisements, the complexity of meaning encompasses both written and visual components. In order to understand the power and meaning of a text that contains multiple modes, such as verbal, visual, and aural, a multimodal analysis of an advertisement is necessary in order to understand the complexities of meaning. The research aims to examine the multimodal resources in the Tokopedia X BTS advertisement on YouTube based on five semiotic multimodal systems proposed by Anstey & Bull (2018). This research employs a qualitative method and a descriptive approach. The data were taken in the form of an image that was taken from a screenshot of the Tokopedia advertisement. The result shows that there are five aspects of the multimodal system contained in this advertisement, namely linguistic, visual, audio, gestural, and spatial. These five aspects are mutually sustainable to convey messages from the Tokopedia application and also advertise and introduce this sophisticated application.